Iodine Iodine level of goats from Shiwalik and middle mountains of north-west Himalayas in relation to soil, fodder, and water status - R A WANI; R SINGH; HIMALINI; A M BHAT; R K BHARDWAJ (Indian Journal of Animal Sciences, 2023)
A baseline survey was carried out to determine the iodine status of goats and its relationship with the levels of soil, water, and fodder samples collected from different agro-climatic zones (sub-tropical, lower, and upper-intermediate) of the Jammu division. A total of 74 blood and 60 milk samples from goats, as well as soil (50), water (50), and fodder (56) samples, were collected. Plasma inorganic iodine (PII), milk inorganic iodine (MII), iodide ion (I-), and thyroid hormone (T3 and T4) levels were measured along with biochemical parameters. The average PII, I-, and MII concentrations of goats from unorganized farms were 55.99±4.56 ng/ml, 1.37±0.11 ppm, and 47.3±5.68 ng/ml compared 74.68±8.40 ng/ml, 1.43±0.11 ppm and 62.01±8.55 ng/ml, respectively from the organized farm. Based on PII level, 71.62% of goats had moderate deficiency (level 50-100 ng/ml) and 28.37% had severe deficiency (level <50 ng/ml). The average levels of iodine in soil and water were 0.24 ppm and 0.06 ppm, respectively. Rabi and kharif fodders showed average iodine levels of 1.25 ppm and 0.37 ppm, respectively. Significant changes were recorded in glucose, HDL and T4 levels. Pearson correlation performed between PII (ng/ml) and biochemical parameters established correlation with T4 (r = -0.465), glucose (r = 0.510), HDL (r = -0.355) and cholesterol (r = 0.271). The study concluded that iodine deficiency is prevalent in the goat population due to lower levels in the environment implying an urgent need for regular supplementation in the diet.